Dinamika Public Private Partnerships dalam Manajemen Sistem e-Ticketing Trans Jogja di Yogyakarta - , RATAMA ARIFIN WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The concept development paradigm of Public Private Partnership (PPPâs) starts changing mindset of both local and central government to adopt it. Government inability beyond ideal of public service delivery, then direct onto an effort to engage private sector and academic sector on public service development. Those condition happens on public service development taken by Yogyakarta local government on Trans Jogja. However, in facts, evidence show development policy product does not satisfying. One of product recently implemented is cashless e-ticketing. This research will analyze the reason cashless e-ticketing policy service management is not optimum yet, kind of support that given by stakeholders and limiting factors on cashless e-ticketing policy management. Methods used in research was qualitative descriptive. Research taken by indepth interview structured toward competent key person. Result showed that each stakeholders support is less optimal. Several factors affecting less optimal implementation its policy, consist of failure toward priority scale option on Trans Jogja development